Evolving trends in the surgical, anaesthetic, and intensive care management of acute spinal cord injuries in the UK - Hasan, Asif; Samuel Tsan, Ern Hung; Argyro, Zoumprouli; Marios C., Papadopoulos; Samira, Saadoun (Springer Nature, 2024)
Purpose We surveyed the treatment of acute spinal cord injuries in the UK and compared current practices with 10 years ago. Methods A questionnaire survey was conducted amongst neurosurgeons, neuroanaesthetists, and neurointensivists that manage patients with acute spinal cord injuries. The survey gave two scenarios (complete and incomplete cervical spinal cord injuries). We obtained opinions on the speed of transfer, timing and aim of surgery, choice of anaesthetic, intraoperative monitoring, targets for physiological parameters, and drug treatments. Results We received responses from 78.6% of UK units that manage acute spinal cord injuries (33 neurosurgeons, 56 neuroanaesthetists/neurointensivists). Most neurosurgeons operate within 12 h for incomplete (82%) and complete (64%) injuries. There is a signifcant shift from 10 years ago, when only 61% (incomplete) and 30% (complete) of neurosurgeons operated within 12 h. The preferred anaesthetic technique in 2022 is total intravenous anaesthesia (TIVA), used by 69% of neuroanaesthetists. Signifcantly more intraoperative monitoring is now used at least sometimes, including bispectral index (91%), non-invasive cardiac output (62%), and neurophysiology (73–77%). Methylprednisolone is no longer used by surgeons. Achieving at least 80 mmHg mean arterial blood pressure is recommended by 70% neurosurgeons, 62% neuroanaesthetists, and 75% neurointensivists. Conclusions Between 2012 and 2022, there was a paradigm shift in managing acute spinal cord injuries in the UK with earlier surgery and more intraoperative monitoring. Variability in practice persists due to lack of high-quality evidence and consensus guidelines.